Physicochemical and Organoleptic Characteristics of Black Noodles with Substitution of Black Soybean Flour and Addition of Glycerol Monostearate - Rahmadini, Fachma Airisa; Winarti, Sri; Putra, Andre Yusuf Trisna (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
Black noodle is an innovative food product formulated by incorporating natural pigment-rich ingredients to enhance visual appeal and nutritional value, setting it apart from conventional noodles. This study aimed to evaluate the effects of black soybean flour substitution and glycerol monostearate (GMS) addition on the physicochemical and organoleptic properties of black noodles, and to determine the optimal formulation. A Completely Randomized Design (CRD) with a factorial pattern was employed, consisting of two factors: black soybean flour substitution (10%, 20%, and 30%) and GMS concentration (1%, 2%, and 3%), with three replications. Data were analyzed using Analysis of Variance (ANOVA), and significant differences were further examined using Duncan’s Multiple Range Test (DMRT) at a 5% significance level. The results indicated that both factors significantly influenced moisture content, protein content, antioxidant activity, elasticity, tensile strength, and sensory attributes. The best mixture was found by using 20% black soybean flour and adding 3% GMS, resulting in a moisture content of 57.23%, protein content of 15.97%, antioxidant activity (IC??) of 312.66 ppm, elasticity of 23.67%, and tensile strength of 0.63 N. Organoleptic evaluations showed favorable responses with scores of 4.28 for color (like), 3.72 for aroma (neutral to like), 3.2 for taste (neutral), and 3.96 for texture (neutral to like). Contribution to Sustainable Development Goals (SDGs): SDG 2 – Zero HungerSDG 3 – Good Health and Well-beingSDG 9 – Industry, Innovation, and InfrastructureSDG 12 – Responsible Consumption and Production